Dampak Kolaborasi Penelitian Pendidikan antara Malaysia dan Indonesia terhadap Perkembangan Ilmu Pengetahuan di Asia Tenggara - Ts. Nurulannisa Binti Abdullah; Leli Hasanah Lubis; Vinda Nur Aisyah (Insan Zenius Ilmiah, 2025)
This study aims to examine in depth the influence of educational research collaboration between Malaysia and Indonesia in supporting the development of science in the Southeast Asian region. Collaboration between countries in the field of research has become an important strategy to face global challenges and improve the quality of higher education. Using a descriptive qualitative approach, this study examines the various forms of academic cooperation that have been established over the past decade, including joint scientific publications, faculty and student exchange programs, the organization of regional scientific conferences, and the establishment of research networks involving institutions from both countries. Data was collected through document reviews, institutional reports, and scientific publications accessed from reputable sources. The results show that Malaysia Indonesia research collaboration contributes significantly to increasing scientific productivity, as shown by the significant upward trend in the number of joint publications from year to year. In addition, this collaboration encourages diversification of fields of study, strengthens cross-cultural knowledge exchange, and shapes a more inclusive and competitive research ecosystem at the regional level. Furthermore, it reinforces Southeast Asia's strategic position as a fast-growing region in contributing to the global knowledge landscape. The study recommends the need for a more structured regional research network, increased investment in cross-border academic cooperation, and harmonization of higher education policies in the region as strategic steps for the future. The findings are expected to serve as a basis for policy makers and stakeholders in designing collaborative strategies that are sustainable and impactful.